2020
DOI: 10.1055/a-1126-4436
|View full text |Cite
|
Sign up to set email alerts
|

Low Level Continuous Heat Wraps can Increase the Efficiency of Transcutaneous Electrical Nerve Stimulation for Pain Management

Abstract: Both transcutaneous electrical nerve stimulation and superficial heat have been used for pain management. While heat has been shown to have a beneficial effect on pain, transcutaneous electrical nerve stimulation remains controversial. The purpose of the present study was to see if heat, when added to transcutaneous electrical nerve stimulation, would provide more consistent relief. A total of 180 subjects participated in this study and were randomly divided into 12 groups. Low level continuous heat was applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Therefore, in this study, taping was applied to compensate for the short application time of TENS. A meta-analysis of TENS for relief from spasticity reported that combining TENS with other treatments could further enhance its effectiveness [11]. Additionally, TENS combined with taping was found to reduce plantar flexor spasticity to a significantly greater extent than only TENS [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in this study, taping was applied to compensate for the short application time of TENS. A meta-analysis of TENS for relief from spasticity reported that combining TENS with other treatments could further enhance its effectiveness [11]. Additionally, TENS combined with taping was found to reduce plantar flexor spasticity to a significantly greater extent than only TENS [25].…”
Section: Discussionmentioning
confidence: 99%
“…Non-invasive treatments, such as splinting, taping, casting, or muscle stretching, can also be effective; however, the frequency and duration of their use are debatable [10]. Transcutaneous electrical nerve stimulation (TENS) is a non-invasive method for pain management with relatively few side effects [11]. Spasticity arises from the disinhibition of the dorsal reticulo-spinal tract, leading to hyper excitability of the stretch reflex mediated by Ia fibers [12].…”
Section: Introductionmentioning
confidence: 99%